Pengaruh Likuiditas, Pertumbuhan Kredit, Efisiensi, dan Kecukupan Modal Terhadap Profitabilitas - Hendrawati, Lia; Djamaludin, Said (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2020)
This study to examine and analyze the effect of liquidity, credit growth, efficiency, and capital adequacy on the Bank’s profitability listed on the IDX partially and simultaneously. The research data are annual data for the 5-year observation period (2009-2013). This research was conducted at 33 banks listed on Indonesia Stock Exchange. Banks Analyzed that met the population criteria were 23 banks. The analytical method used in multiple linier regression. The results showed that liquidity, credit growth, efficiency, and capital adequacy together (simultaneously) significantly influence profitability. Partially, liquidity has a significant positive effect on profitability, while efficiency has a significant negative effect. Credit growth and capital adequacy have no significant effect on profitability. Liquidity is the variable that has the biggest effect on the Bank’s profitability.